PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MAKANAN DAN MINUMAN - Theopratama, Samuel Ekawira; Bangun, Nurnainun (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study was to determine the effect of profitability, leverage, and liquidity on financial distress in food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. This study used 93 company data and used purposive sampling method. The results showed that profitability and liquidity have a positive effect on financial distress, while leverage has a negative and insignificant effect on financial distress.